(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud services will eliminate the need to install and manage client rich applications and further its scope in all the private sector would increase thus it would help the company to reduce high cost infrastructure and maintenance cost. . In this paper we are surveying the security related issues in the field of cloud computing. We will discuss the different techniques regarding the data privacy and also the advancement in these techniques .This paper evaluates different data privacy techniques involved in Cloud computing and then proposing the most optimized technique. This paper focuses on the usage of Cloud services and security issues to build these cross-domain Internet-connected collaborations